2022
DOI: 10.1093/tropej/fmac053
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Pathophysiology and Mortality of Shock in Children in Low (Middle) Income Countries: A Systematic Review

Abstract: Objectives Shock is a life-threatening condition in children in low- and middle-income countries (LMIC), with several controversies. This systematic review summarizes the etiology, pathophysiology and mortality of shock in children in LMIC. Methods We searched for studies reporting on children with shock in LMIC in PubMed, Embase and through snowballing (up to 1 October 2019). Studies conducted in LMIC that reported on shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
1
7
1
Order By: Relevance
“…A possible explanation could be prior antibiotic administration which may have lowered prevalence of bacteraemia in our population. The organisms we found are in line with prior research from African settings [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation could be prior antibiotic administration which may have lowered prevalence of bacteraemia in our population. The organisms we found are in line with prior research from African settings [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…highlighted significant disparities in access to trauma care within and across sub‐Saharan African countries, but there are significant gaps in trauma‐specific data, as evidenced by the fact that less than half of countries were represented in the review. Assies et al 43 . reviewed 959 studies from LMICs and found that the etiology, pathophysiology, and mortality trends of shock are still poorly understood, most likely as a result of heterogenous definitions of shock in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of shock is ranging from 1.5% in hospitalized children, to 44.3% in critically ill children. 1 When left untreated or detected late, hypovolemic condition could be fatal and might cause death. Early detection and correction of hypovolemia can restrict hypoxic damage, relieve tissue hypoxia, enhance the clinical outcome of critically ill patients, and thus, might save the patient's life.…”
Section: Introductionmentioning
confidence: 99%